2001
DOI: 10.1152/ajpregu.2001.281.1.r162
|View full text |Cite
|
Sign up to set email alerts
|

Role of the hepatic function in the development of the pyrogenic tolerance to muramyl dipeptide

Abstract: We have demonstrated that the hepatic function may have an important role in the development of tolerance to the pyrogenic effect induced by endotoxin. To further investigate if the role of the hepatic function in the development of tolerance also extends to that induced by other pyrogenic stimuli, we investigated the effect of galactosamine, a specific inhibitor of the hepatic protein synthesis, on the development of tolerance to the pyrogenic effect induced by muramyl dipeptide (MDP) in rats. Pyrogenic toler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Those stimuli include peptidoglycan, 25-hydroxy-cholesterol, tissue ischemia, and surgical stress [27][28][29][30]. In this study, we demonstrated that portal congestion and subsequent visceral congestion also induced LPS tolerance in rats following PTO.…”
Section: Discussionmentioning
confidence: 50%
“…Those stimuli include peptidoglycan, 25-hydroxy-cholesterol, tissue ischemia, and surgical stress [27][28][29][30]. In this study, we demonstrated that portal congestion and subsequent visceral congestion also induced LPS tolerance in rats following PTO.…”
Section: Discussionmentioning
confidence: 50%
“…At least some TLR2 agonists from Gram-positive bacteria are known to cause fever when injected in rats (6,14), guinea pigs (17,35), rabbits (3), and cats (2). Neither does the present study rule out the possibility that LPS causes some of its thermoregulatory effects by acting on receptors other than TLR4.…”
Section: Discussionmentioning
confidence: 63%
“…4 This refractory state of the host is not solely induced by LPS (endotoxin) but also by various other PAMPs. 5,6 Although the molecular mechanisms are not fully understood, 4 PAMP-mediated tolerance is characterized by a transient inactivation of TLR-mediated induction of distinct inflammatory genes (e.g. TNF-α).…”
Section: Introductionmentioning
confidence: 99%